2016
DOI: 10.1155/2016/2920370
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Calcium Acetate Manufactured with Etching Waste Solution and Limestone Sludge as a Cementitious High-Early-Strength Admixture

Abstract: Concrete is one of the most widely used construction materials. There are several methods available to improve its performance, with one of them being the use of high-early-strength admixtures (HESAs). Typical HESAs include calcium nitrate, calcium chloride, and calcium formate (CF). Industrial by-products, such as acetic acid and lime stone sludge (LSS), can be used together to produce calcium acetate (CA), which can subsequently be used as a cementitious HESA. In this study, calcium carbonate and LSS were mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…CA has been extensively reported as a promising chemical for environmental and industrial applications [28]. CA can be used in the environmental field, as the best alternative material for replacing the corrosive and environmentally unacceptable deicers (sodium chloride and calcium chloride) [23], as a powerful SO 2 , NO X , and toxic particulate emission control agent in coal combustion processes to reduce acid rain [29], as an effective catalyst for the facilitation of coal combustion [30], and as an adsorbent of carbon dioxide [31].…”
Section: Introductionmentioning
confidence: 99%
“…CA has been extensively reported as a promising chemical for environmental and industrial applications [28]. CA can be used in the environmental field, as the best alternative material for replacing the corrosive and environmentally unacceptable deicers (sodium chloride and calcium chloride) [23], as a powerful SO 2 , NO X , and toxic particulate emission control agent in coal combustion processes to reduce acid rain [29], as an effective catalyst for the facilitation of coal combustion [30], and as an adsorbent of carbon dioxide [31].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work confirmed that mixing 1% calcium acetate manufactured from limestone sludge with 1 wt% cement could accelerate the hydration of cement and improve its early strength (Kim et al 2016). Figure 1 shows the corrosion characteristics of several types of inhibitors against chloride ions.…”
Section: Introductionmentioning
confidence: 76%
“…Calcium acetate was used as a promising chemical for environmental and industrial applications [25]. In the environmental eld, it was employed as an alternative compound to replace corrosive deicers with environmentally unacceptable properties such as calcium chloride (CaCl 2 ) and sodium chloride (NaCl) [26].…”
Section: Introductionmentioning
confidence: 99%